2021
DOI: 10.7717/peerj.11754
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of biochar and chicken manure on maize (Zea mays L.) growth, lead uptake and soil enzyme activities under lead stress

Abstract: The goal of the present work was to evaluate the additive effects of biochar and chicken manure on maize growth in Pb-contaminated soils. In this study, we conducted a pot experiment to investigate how biochar in soil (20, 40 g·kg−1), chicken manure in soil (20, 40 g·kg−1), or a combination of biochar and chicken manure in soil (each at 20 g·kg−1) effect maize growth, Pb uptake, leaves’ antioxidant enzymatic activities, and soil enzyme activities under artificial conditions to simulate moderate soil pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 87 publications
2
17
0
Order By: Relevance
“…Concerning the effect of biochar on grain nutrient contents of maize and wheat plants, as shown in Figure 4, the application of CSMB increased plant N, P and K contents in both plants with average values of 77.48 mg•g −1 DW, 25.87 mg•g −1 DW and 3.5 mg•g −1 DW for wheat plants and 24.18 mg•g −1 DW, 12.25 mg•g −1 DW, and 2.98 mg•g −1 DW for maize plants, respectively. These results are in the same direction as [86]. Inal et al [87] reported that biochar application increased the growth and N, P, K, Ca, Zn, Cu and Mn concentrations of maize and bean plants.…”
Section: Plant Biomasssupporting
confidence: 70%
“…Concerning the effect of biochar on grain nutrient contents of maize and wheat plants, as shown in Figure 4, the application of CSMB increased plant N, P and K contents in both plants with average values of 77.48 mg•g −1 DW, 25.87 mg•g −1 DW and 3.5 mg•g −1 DW for wheat plants and 24.18 mg•g −1 DW, 12.25 mg•g −1 DW, and 2.98 mg•g −1 DW for maize plants, respectively. These results are in the same direction as [86]. Inal et al [87] reported that biochar application increased the growth and N, P, K, Ca, Zn, Cu and Mn concentrations of maize and bean plants.…”
Section: Plant Biomasssupporting
confidence: 70%
“…The applica-tion of biochar regulates the synthesis of antioxidant enzymes in pearl millet plants and therefore improves salt stress resistance [ 43 , 44 ]. The positive role of biochar in re-ducing oxidative stress was attributed to the reduction in malondialdehyde (MDA) concentrations, resulting in higher growth [ 43 , 45 , 48 , 49 , 50 , 51 ]. The application of the highest dose of shrimp waste-derived biochar (2.5%) increased the soluble carbohydrates and proline by 75 and 60% and reduced MDA by 32% in comparison with the nonamended soil.…”
Section: Discussionmentioning
confidence: 99%
“…Varshney et al [54] and Cruz et al [33] have also emphasized that high ash doses applied may cause excessive soil salinity, thereby ultimately contributing to worse conditions for plant growth and root development. However, previous investigations conducted by Liu et al [1] and Romdhane et al [31] proved that wood-based ash applied in doses from 20 to 40 g kg −1 soil might positively affect Zea mays L. biomass. Differences observed for ash effects in the present study and experiments of the aforementioned authors are mainly due to the differences in the chemical composition of the analyzed ashes.…”
Section: Correlations Between the Analyzed Parametersmentioning
confidence: 91%
“…Zea mays L. belongs to the Poaceae family. Due to its high yield potential and nutritional value, it is cultivated in many regions across the world for food and feed production purposes [1,2]. It is also commonly used as a main energy crop for biogas production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation